The Role of Institutions: A Cross-country Analysis of Renminbi Trading in Foreign Exchange Markets - Marina Zucker-Marques; Pedro Perfeito da Silva (China & World Economy, 2022)
We explore how China's geographically targeted policies impact RMB overseas use individually or in combination. The policies include swap agreements, clearing banks, investment quotas, and direct trading between Chinese renminbi (RMB) and non-USD currencies. Adopting a fuzzy-set qualitative comparative analysis and using Bank of International Settlements cross-country data on foreign exchange markets, we find that institution building has lowered the barriers to international adoption of the RMB. Specifically, for countries economically close to China, high RMB trading is explained by either (i) having a clearing bank in the host market and direct quotations between the RMB and the local currency, or (ii) being a financial center and having access to the Chinese capital market. This combination of policies is explained by the creation of (i) “trading posts” that provide RMB liquidity abroad, and (ii) channels that allow actors to “recycle” offshore RMB funds. We triangulate our results with interviews conducted with senior People's Bank of China officials.
Keywords: 330; foreign exchange markets; fuzzy-set qualitative comparative analysis; institutional context; international monetary system; offshore RMB trading; RMB internationalization